PENGARUH CITRA MERK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA MIO - Ratih Dwi Pratiwi; Imam Wibowo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
This research aimed to analyze the influence of a brand image and quality product on purchase decision of Yamaha Mio motorcycle partially and simultanously. This was a quantitative research by a survey method. The research population were users of Yamaha Mio motorcycle. Sample taking technique used a purposive sampling method with samples numbered 100 respondent. Based on regression analyze, The research results showed that brand image positively and significant influence a purchase decision of Yamaha Mio motorcycle, and product quality positively and significant influence a decision purchase of Yamaha Mio. Brand image and product quality simultanously positively and significant influence purchase decision of Yamaha Mio motorcycle.